A Systematic Review of the Efficacy and Availability of Targeted Treatments for Central Sensitization in Women With Endometriosis. Issue 10 (1st October 2022) - Simpson, Grace; Philip, Moira; Lucky, Tarana; Ang, Catarina; Kathurusinghe, Shamitha
Abstract : Objectives: Central sensitization (CS) contributes to patient variability when treating pain in endometriosis. Targeting this process may alleviate hyperalgesia and allodynia in women refractory to current treatments. Currently, there has been no review of targeted treatments for central sensitization in women with endometriosis. Therefore, this review aims to identify and summarize the findings of studies regarding the availability and efficacy of targeted treatments for CS in women with endometriosis. Materials and Methods: A systematic review was conducted searching MEDLINE, Embase and CINAHL. Inclusion criteria: primary research articles, women with endometriosis and CS features, and description of treatments for CS, or its effects on hyperalgesia and allodynia. Exclusion criteria: review articles, letters to the editor, commentaries, editorials, protocols, or women with endometriosis infiltrating nerves. Risk of bias analysis was conducted. Data was reviewed and summarized by treatment method. Results: Eight studies met inclusion criteria, demonstrating limited research in this area. Four treatment options were addressed: surgical approaches, nerve stimulation approaches, injection-based therapies, and hormonal therapies. Surgery and nerve stimulation appear the most promising treatments for CS. Injections have limited and mixed evidence of efficacy. Limited evidence suggests hormonal therapies may be ineffective. Discussion: Given the lack of evidence for any treatment, all require further research to determine treatment efficacy before options will be available clinically. There is a clear need for consistency in defining and identifying CS in study populations. This review identifies areas of interest, particularly surgery and nerve stimulation, from which future research must stem.